2012
DOI: 10.1007/s00210-012-0781-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of antidepressant and antipsychotic drugs with the human organic cation transporters hOCT1, hOCT2 and hOCT3

Abstract: Besides the three antidepressant-sensitive, Na(+)- and Cl(-)-dependent monoamine transporters, Na(+)-independent organic cation transporters (OCTs) are known to transport monoamines. However, little is known about the interactions of psychotropic drugs with human (h) OCTs. In the present study, a series of diverse antidepressant and antipsychotic drugs were examined for their inhibitory potency at hOCT1, hOCT2 and hOCT3 by measuring inhibition of [(3)H]-MPP(+) uptake into HEK293 cells stably expressing one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…Given that substrate-dependent inhibition has been reported for OCT2 (Belzer et al, 2013) and multidrug and toxin extrusion protein 1 (Martínez-Guerrero and Wright, 2013), comparison of the IC 50 values obtained in the present study with previously reported values obtained using other substrates might give some insight into how different substrates are handled by OCT1. Previously, diphenhydramine and fluoxetine inhibited MPP + uptake with IC 50 values of 3.4 mM and 2.8 mM, respectively (Müller et al, 2005;Haenisch et al, 2012), and verapamil inhibited TEA + transport with an IC 50 of 2.9 mM (Zhang et al, 1998). These values are comparable to the IC 50 values we obtained for OCT1-mediated uptake of serotonin, which suggests that serotonin and the two model substrates MPP + and TEA + are transported in a similar way by OCT1.…”
Section: Discussionmentioning
confidence: 98%
“…Given that substrate-dependent inhibition has been reported for OCT2 (Belzer et al, 2013) and multidrug and toxin extrusion protein 1 (Martínez-Guerrero and Wright, 2013), comparison of the IC 50 values obtained in the present study with previously reported values obtained using other substrates might give some insight into how different substrates are handled by OCT1. Previously, diphenhydramine and fluoxetine inhibited MPP + uptake with IC 50 values of 3.4 mM and 2.8 mM, respectively (Müller et al, 2005;Haenisch et al, 2012), and verapamil inhibited TEA + transport with an IC 50 of 2.9 mM (Zhang et al, 1998). These values are comparable to the IC 50 values we obtained for OCT1-mediated uptake of serotonin, which suggests that serotonin and the two model substrates MPP + and TEA + are transported in a similar way by OCT1.…”
Section: Discussionmentioning
confidence: 98%
“…At all events, whether it was so assumed or not, we can find evidence for interactions with transporters for each of the other drugs except for antipyrine, carbamazepine, and terbutaline. These are: α-methyldopa (Uchino et al, 2002), amoxicillin (Li et al, 2006; Sala-Rabanal et al, 2006; Fujiwara et al, 2011, 2012), atenolol (Kato et al, 2009), cimetidine (Collett et al, 1999; Burckhardt et al, 2003; Motohashi et al, 2004; Pavek et al, 2005; Matsushima et al, 2009; Tsuda et al, 2009), creatinine (Schömig et al, 2006; Chen et al, 2009; Zhou et al, 2009; Hosoya and Tachikawa, 2011; Tachikawa and Hosoya, 2011; Torres et al, 2011), desipramine (Wu et al, 2000; Haenisch et al, 2012), enalapril (Pang et al, 1998), enalaprilat (Ishizuka et al, 1998), fluvastatin (Varma et al, 2011; Sharma et al, 2012), furosemide (Uwai et al, 2000a; Eraly et al, 2006; Vallon et al, 2008), hydrochlorothiazide (Race et al, 1999; Uwai et al, 2000a; Hasannejad et al, 2004; Han et al, 2011), ketoprofen (Khamdang et al, 2002; Morita et al, 2005), Lisinopril (Knütter et al, 2008), losartan (Edwards et al, 1999; Race et al, 1999; Knütter et al, 2009; Sato et al, 2010), metoprolol (Dudley et al, 2000), naproxen (Apiwattanakul et al, 1999; Mulato et al, 2000; Khamdang et al, 2002; El-Sheikh et al, 2007), piroxicam (Jung et al, 2001; Khamdang et al, 2002), propranolol (Dudley et al, 2000; Wang et al, 2010a; Kubo et al, 2013b; Zheng et al, 2013), ranitidine (Collett et al, 1999; Müller et al, 2005; Ming et al, 2009), and verapamil (Döppenschmitt et al, 1999; Kubo et al, 2013a). We have also plotted (Figure 7) data from the Oral Drugs in the Core WHO Essential Medicines List (Table 2 of Kasim et al, 2004).…”
Section: We Propose Some Candidate Discriminating Experiments That Admentioning
confidence: 99%
“…Whereas high-affinity sodium cotransporters for serine (SERT), dopamine (DAT) and epinephrine (NET) in presynaptic nerve endings terminate local receptor activations, the tonus of monoamine neurotransmitters is modulated by transporters in the blood--brain barrier, the choroid plexus and plasma membranes of neurons and glial cells. After the early demonstration that OCTs transport monoamine neurotransmitters and are expressed in the brain [3,43-45], many years passed until functional roles of OCTs in brain were demonstrated experimentally [46][47][48][49][50][51][52][53][54][55][56][57]. OCT1 has been localized to the bloodbrain barrier [46,47], OCT2 to the blood-brain barrier, neurons and the choroid plexus [43,[46][47][48][49][50][51], and OCT3 to neurons and glial cells [49,[52][53][54].…”
Section: Octs In Brainmentioning
confidence: 99%
“…OCT1 has been localized to the bloodbrain barrier [46,47], OCT2 to the blood-brain barrier, neurons and the choroid plexus [43,[46][47][48][49][50][51], and OCT3 to neurons and glial cells [49,[52][53][54]. OCT1 and OCT2 facilitate the passage of cationic drugs and xenobiotics across the blood-brain barrier, whereas OCT2 and OCT3 modulate concentrations of monoamine neurotransmitters, cationic drugs and toxins within brain interstitium [48,[55][56][57][58]. Experiments employing OCT2-and OCT3-deficient mice and specific inhibitors showed that these transporters provide an alternate monoamine clearance system that operates distant from the nerve terminals.…”
Section: Octs In Brainmentioning
confidence: 99%